Hypokalemia-Induced Rhabdomyolysis as a result of Distal Renal Tubular Acidosis in a Pregnant Woman: A Case Report and Literature Review - Manasawee Srisuttayasathien (Hindawi Limited, 2015)
Rhabdomyolysis in pregnancy is a rare occurrence. The manifestation of distal renal tubular acidosis (RTA) for the first time during adulthood is uncommon. According to a review of the literature, pregnancy may predispose individuals to rhabdomyolysis due to hypokalemia. A reduction in interstitial potassium ions could decrease muscular blood flow and lead to muscle injury. This report describes the case of a pregnant woman with rhabdomyolysis induced by hypokalemia resulting from distal RTA. The patient subsequently delivered a healthy newborn.